Modelling of Tsunami Forces on Coastal Structures: a Review - Govindasamy, N.; Mardi, N.H.; Malek, M.A. (International Journal of Engineering and Technology, 2018)
This paper reviews methods applicable to assess the impact of tsunami forces on coastal structures. Countries affected by tsunamis have proven that this environmental disaster has costed billions of losses, such as the event occurred during year 2004 Andaman tsunami. Therefore, there is a need to assess the structural behaviour upon the impact of tsunami forces in order to minimize the damages and to ensure that coastal structures are able to sustain loading from high current-velocity waves. Currently in practice, there are two approaches of accessing the impacts of tsunami on structures namely physical modelling and experiment or numerical modelling and simulation. Numerical modelling methods are expected to produce acceptable analysis on the stability and condition of structures subjected to tsunami loadings since it incorporates several important parameters which are not implemented in physical modelling. The result from this study is expected to prompt engineers and relevant authorities to revise the current design guidelines on coastal structures which could sustain possible tsunami event in the future.